Autism Spectrum Disorders in Calabar, Nigeria - Torty, Chimaeze; Eyong, Komomo; Asindi, Asindi Andrew; Usun, Edet (Iranian Journal of Child Neurology, 2024)
Objectives Autism spectrum disorder (ASD) is a neurodevelopmental disorder that is prevalent worldwide. The incidence of autism has increased worldwide. However, there is a dearth of data in sub-Saharan Africa. The study is aimed at determining the clinical and socio-developmental profile of children with ASD in a tertiary hospital in Nigeria. Materials & Methods This study is a six-year retrospective review of the medical records of children who presented with clinical autism diagnoses at the Department of Pediatrics, University of Calabar Teaching Hospital. Relevant data were extracted from the medical records of those who met the diagnostic criteria. Descriptive statistics were presented in proportions, percentages, and tables. Results Of the 1806 children with neurological disorders seen in the clinic within the study period, twenty-eight were found to have symptoms of autism based on the American Psychiatric Association›s Diagnostic and Statistical Manual V (DSM -5) criteria, giving a prevalence of 1.6%. The mean age at diagnosis was 3.8 ±1.4 (range 2 to 10) years, with a male-to-female ratio of 3:1. About two-thirds of the children diagnosed were older than three years. Seven percent of the children had siblings with autism, 53.5% of children with autism in the study had hyperactivity as comorbidity, while seizures were found in 7% of cases. Conclusion The prevalence of ASD among children seen in Calabar is 1.6%. Hyperactivity, mental retardation, and seizure disorders are associated comorbidities in the study. Late presentation is a common feature in this facility. Thus, increasing awareness is essential to enhance early recognition, timely diagnosis, and appropriate intervention